Optimalisasi Audit Siklus Aset Tetap Melalui Evaluasi Pengendalian Internal dan Analisis Risiko Audit - Yunisa Sri Wahyuni; Rian Ridwan; Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines the role of internal auditing in strengthening the effectiveness of fixed asset control within an organization through a descriptive qualitative approach supported by document analysis and literature review. The research highlights how structured audit procedures, supported by adequate documentation and consistent monitoring, contribute significantly to improving the accuracy and reliability of fixed asset records. The findings show that effective internal control systems, when integrated with competent audit practices, can reduce the risk of misstatements, asset misuse, and irregularities that may disrupt operational stability. Furthermore, the use of technology in asset monitoring, regular evaluations, and enhanced auditor competence play a crucial role in promoting transparency and accountability. This study underscores that the audit of fixed assets functions not only as a verification mechanism but also as a strategic instrument to support sustainable governance. The results are expected to provide practical insights for organizations seeking to optimize their asset management and internal audit processes to achieve better operational performance and financial integrity.